Determining dynamic processes in a tank after its separation from the bottom during a fire - Nesukh, Mykhailo; Subota, Andriy; Shvydenko, Andrii; Nekora, Olga; Kulitsa, Oleh; Kropyva, Mykhailo (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the process of separating the body of a vertical steel tank from the bottom under the influence of emergency thermal and dynamic loads characteristic of fires at tank farms. The task addressed was to predict parameters of the trajectory of movement of a vertical steel tank with fuel when it is separated under the action of internal excess pressure due to the thermal effects of a fire. The dynamic processes of destruction of the weld at the bottom of the tank enclosure and the processes of fuel leakage from it were investigated. During the research, a computer model of the process of separation of a part of the tank was substantiated, which takes into account the geometric and physical nonlinearity of the material behavior under such conditions, as well as hydrodynamic processes during fuel leakage. Computer simulation showed that the height of the tank’s flight when it is separated from the bottom depends on its filling level and total volume. At the same time, a lower filling level of the tank and its smaller volume determine a lower height of its bouncing. This is explained by the fact that the increase in the weight of the mechanical system, which is a tank with an oil product, leads to an increase in energy for the corresponding bouncing height. To describe the revealed patterns, a regression analysis was conducted. As a result, empirical dependences were established between the kinematic parameters of the bouncing trajectory, the design characteristics of the tank, and its filling level. The acceptable adequacy of the data obtained by the revealed regression dependence was shown. The revealed patterns are a scientific basis for compiling practical recommendations on technological requirements for storing oil products in vertical tanks to reduce the risk of their bouncing over long distances during an internal explosion due to a fire